Polyphenolic profile by FIA/ESI/IT/MSn and antioxidant capacity of the ethanolic extract from the barks of Maytenus cajalbanica (Borhidi & O. Muñiz) Borhidi & O. Muñiz - Pino, Liudis L.; García, Trina H.; Delgado-Roche, Livan; Rodeiro, Idania; Hernández, Ivonne; Vilegas, Wagner [UNESP]; Spengler, Iraida (Taylor & Francis, 2019)
Medium and high polarity extracts from Maytenus species are known to contain polyphenolic compounds such as proanthocyanidins. The high polarity and structural complexity of these compounds make very difficult their isolation even by modern chromatographic techniques. Maytenus cajalbanica (Borhidi & O. Muñiz) Borhidi & O. Muñiz is endemic from Cuba. So far, there are reports neither of phytochemical work nor of biological evaluation of extracts from this subspecies. The goal of this work is to determine the polyphenolic profile and the antioxidant capacity of the ethanolic extract from the barks of Maytenus cajalbanica. FIA/ESI/IT/MSn analysis allowed the identification of 5 flavan-3-ol monomers, 33 proanthocyanidins, 2 free flavonoids and their respective glycosides as major compounds of the ethanolic extract, which showed a strong radical scavenging capacity and a significant ferric reduction power. FIA/ESI/IT/MSn technique led the rapid, effective and sensitive determination of the polyphenolic profile of Maytenus cajalbanica without previous separation.
Keywords: antioxidant activity; Celastraceae; FIA/ESI/IT/MSn; Maytenus; proanthocyanidins